Current Opinions on the Clinical Utility of Ravulizumab for the Treatment of Paroxysmal Nocturnal Hemoglobinuria - Gurnari C; Nautiyal I; Pagliuca S (Dove Medical Press, 2021)
Carmelo Gurnari,1,2 Ishani Nautiyal,1 Simona Pagliuca1,3 1Department of Translational Hematology and Oncology Research, Taussig Cancer Center, Cleveland Clinic Foundation, Cleveland, OH, USA; 2Department of Biomedicine and Prevention, PhD in Immunology, Molecular Medicine and Applied Biotechnology, University of Rome Tor Vergata, Rome, Italy; 3ED561 Hematology, Oncogenesis and Biotherapies, University of Paris, Paris, FranceCorrespondence: Carmelo GurnariTranslational Hematology and Oncology Research, Cleveland Clinic Foundation, 9620 Carnegie Ave, Building NE6-250, Cleveland, OH, 44106, USAEmail carmelogurnari31@gmail.comAbstract: Paroxysmal nocturnal hemoglobinuria (PNH) is a rare disorder of hematopoietic stem cells genetically defined by the acquisition of somatic mutations in the X-linked phosphatidylinositol glycan anchor biosynthesis, class A (PIGA) gene. PIGA is essential for the synthesis of glycosyl phosphatidylinositol (GPI) anchor proteins and its mutations result in a deficiency of such molecules on the membrane of blood cells derived from the mutant clone. In particular, the lack of the GPI-linked complement regulatory proteins CD55 and CD59 is responsible for the increased sensitivity of PNH erythrocytes to complement-mediated destruction. Indeed, the classical clinical picture of PNH includes signs and symptoms of intravascular hemolysis along with variable degrees of cytopenia and a strong tendency to thrombosis, hallmarks of the disease. Before the introduction of anti-complement inhibitors, PNH was characterized by a high mortality primarily due to thrombotic events. The approval of the terminal anti-complement inhibitor eculizumab in 2007 introduced a paradigm shift in the treatment of the disease with improvement of the chronic hemolytic process and dramatic reduction of the thrombotic rate. However, eculizumab has a relatively short half-life when considering a life-long treatment, with obvious consequences as to the quality of life of treated patients necessitating relatively frequent drug administrations. Moreover, up to 30% of PNH patients undergoing eculizumab therapy show a suboptimal response, continuing to require red cell transfusions because of extravascular hemolysis or breakthrough hemolytic episodes. In 2019, the FDA approved the second-generation C5 inhibitor ravulizumab, a long-lasting agent with a better control of disease manifestations. Herein, we discuss the use of ravulizumab in PNH, its differences with first-generation C5 inhibitors, the research evidence supporting the safety and efficacy of this drug and its impact on costs for health systems and quality of life of PNH patients.Keywords: paroxysmal nocturnal hemoglobinuria, ravulizumab, anti-complement therapy